Beneficios económicos de un sistema de control interno para el incremento de productividad en el sector artesanal de fabricación de muebles de la ciudad de Guayaquil - Arias Domínguez, Mariuxi Elena (2018)
The present work makes an evaluation of the situation of the Ecuadorian artisan sector that works with wood, through surveys and interviews to the guild mentioned. This economic sector has great potential due to the fact that it has raw material of very good quality, due to the great forest wealth with which Ecuador has; another of the strengths is the skill of the craftsmen who often transmit that profession as a family tradition. However, this productive segment suffers from an evil that does not allow it to obtain the desired profitability: informality and lack of controls. Given this situation, this research proposes an internal control system to establish processes and controls that generate cost savings, increase productivity and increase economic benefits for the artisan and his business….